2024
DOI: 10.3390/encyclopedia4010007
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins and Bacteriophages as Dual Biological Players for Food Safety Applications

Nacim Barache,
Yanath Belguesmia,
Beatriz Martinez
et al.

Abstract: The development of new techniques for the control of pathogenic microorganisms during food production and for the prevention of spoilage are needed to reduce or replace chemical preservatives. This is due to the trend that consumers are increasingly questioning the use of chemical preservatives because of the many health concerns. Because of this issue, bacteriocins and bacteriophages are increasingly viewed as safe natural preservatives with a long history of various applications during food production and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…In our instance, genomic analysis revealed that MATE 2 possesses an endolysin ( Figure 2 ), which can also be used against Xf. Furthermore, recent findings showed that phages exhibit anti-biofilm properties against various pathogenic bacteria, including Escherichia coli , Enterococcus faecium , and Enterococcus faecalis ( Melo et al, 2019 ; Chaudhary et al, 2022 ), as well as the capacity to act synergistically with other natural antimicrobials, such as bacteriocins and natural antimicrobial peptides ( Barache et al, 2024 ). These findings encourages the exploration of MATE 2’s efficacy and its endolysin against Xf biofilm within the plant vascular system and their potential synergies with existing therapeutic agents to develop a more robust and integrated Xf disease control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In our instance, genomic analysis revealed that MATE 2 possesses an endolysin ( Figure 2 ), which can also be used against Xf. Furthermore, recent findings showed that phages exhibit anti-biofilm properties against various pathogenic bacteria, including Escherichia coli , Enterococcus faecium , and Enterococcus faecalis ( Melo et al, 2019 ; Chaudhary et al, 2022 ), as well as the capacity to act synergistically with other natural antimicrobials, such as bacteriocins and natural antimicrobial peptides ( Barache et al, 2024 ). These findings encourages the exploration of MATE 2’s efficacy and its endolysin against Xf biofilm within the plant vascular system and their potential synergies with existing therapeutic agents to develop a more robust and integrated Xf disease control strategy.…”
Section: Discussionmentioning
confidence: 99%